Land Tenure and Farmers Income Distribution (Case Temon and Keduang Watershed) - Cahyono, S Andi; Haryanti, Nana (Universitas Muhammadiyah Surakarta, 2002)
Land authority and imbalance of income distribution are always be an interesting issue for an importance role of land in society. It is interesting and necessary to find out how contribution of agricultural sector to farmer income and what effect of land authority imbalance to income distribution. This research was conducted at Temon and Keduang sub watershed. Survey method was adapted to collect the field data. Afterward, the collected data was analyzed quantitatively. The result indicated that the contribution of agricultural sector to farmer income at Temon sub watershed (69.39%) was hhigher than at Keduang sub watershed (59.11%). This showed that narrow in land authority will be increasing the contribution of agricultural sector to total income. It related to diversify efforts of land using. Imbalance of land authority not always affected the income imbalance, caused by development of non agricultural sector. Land access only was unfeasible to be an indicator of farmers household income level without considering the biophysics condition and non agricultural sector growth development.